Epitelo-mezenchymální tranzice v nádorové tkáni a její role při metastatickém šíření karcinomů - Matějka, V M; Fínek, J; Králíčková, M (Klinicka onkologie, 2017)
BACKGROUND: Metastasis, recurrence, and resistance to chemotherapy are leading causes of the majority of cancer-related mortality worldwide. The process of metastasis can be artificially divided into a series of sequential, highly organized, and organ-specific steps. The underlying mechanisms are still poorly understood, but are believed to be mediated by epithelial-mesenchymal transition (EMT). First described in embryogenesis, EMT is a cellular reprogramming process in which epithelial cells acquire a mesenchymal phenotype. During this transformation, epithelial cells lose their shape, epithelial markers, and ability to grow in colonies. They acquire a spindle-shaped morphology and exhibit more motile and invasive behavior. These phenotypic changes are associated with modifications in different interconnected protein and gene families, such as transcription factors, cadherins, catenins, matrix metalloproteases, and growth receptors. EMT has been observed in many cancers, such as breast, ovarian, colon, and esophageal cancers, and is associated with poor prognosis and metastasis. Also, resistance to cytotoxic treatments is associated with reactivation of embryonic programs. Understanding this process is necessary to provide a better understanding of cancer progression and could lead to the development of new therapeutic or prognostic strategies for the treatment of cancer. CONCLUSION: This article summarizes the known molecular pathways involved in EMT in cancer.Key words: epithelial-mesenchymal transition - carcinoma - metastasisThe authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study.The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers.Submitted: 24. 6. 2016Accepted: 14. 11. 2016.
Keywords: Hedgehog Proteins; Drug Resistance, Neoplasm; Neoplasms; lidé; Humans; Wnt Signaling Pathway; mikro RNA; Receptors, Notch; epitelové buňky; Epithelial Cells; chemorezistence; receptory Notch; Neoplasm Metastasis; transformující růstový faktor beta; proteiny hedgehog; nádory; Transforming Growth Factor beta; MicroRNAs; kadheriny; signální dráha Wnt; Epithelial-Mesenchymal Transition; Cadherins; epitelo-mezenchymální tranzice; metastázy nádorů